The Experimenter's Body: Movement as an Artifact - Thaisa Martins (EXARC Journal)
This paper  summarises a part of the discussions carried out in the author's MA in Archaeology at the Federal University of Rio de Janeiro - Brazil. Starting from the question “when the only thing we have is the archaeologist’s body, how can we do archaeology?” We propose to engage with methodologies and theories from the field of Dance to analyse the experimenter’s body in experimental archaeology research. Body Techniques (Mauss, 1973) and extra-daily body technique (Barba, 1995) are key concepts for understanding the idea of artifactual movement proposed in this research. As a result, we are proposing a trans-disciplinary methodology to work with the body movement from an archaeological perspective, using Rudolf Laban’s Choreology and Helenita Sá Earp’s Fundamentals of Dance Theory.